Cu-Cu bonding in ambient environment by Ar/N 2 plasma surface activation and its characterization - Chua, Shen Lin (2020)
Ar/N 2 plasma surface activation in ambient environment for Cu-Cu bonding has been performed and characterized. Cu-Cu bonding occurs at room temperature and under normal atmospheric conditions. Postbonding annealing is performed at 300 °C and below to control the overall thermal budget. Shear strength and hermeticity property of samples with varying annealing temperature are investigated. Samples annealed at 250 °C demonstrate the highest average shear strength of 20.3 MPa and the lowest average helium leak rate of 8.7×10 -9 atm cc/s. Daisy chain structures are used to examine the electrical property of sample bonded at 300 °C, and the temperature cycling tests from -40 °C to 125 °C for 1000 cycles have been performed for the reliability assessment. It is observed that the dies are well-bonded and intact after 1000 cycles even though the exposed Cu surface is heavily oxidized.